2005
DOI: 10.1103/physrevb.71.092504
|View full text |Cite
|
Sign up to set email alerts
|

Surface pinning in an amorphous ZrTiCuNiBe alloy

Abstract: We have measured the amplitude and the phase of an electromagnetic ͑EM͒ field radiated from a superconductor ͑amorphous ZrTiCuNiBe alloy͒ in the mixed state due to the interaction of the flux lattice with an elastic wave. The results point to an essential contribution of a surface pinning into the flux lattice dynamics. We propose a model that describes radiation of the EM field from superconductors with nonuniform pinning. The model allows us to reconstruct the viscosity and the Labusch parameters from the ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…This question is studied in detailed in Ref. 5. It is shown that the nonuniformity of 0 ͑the decrease of the conductivity of a layer near the surface͒ increases the phase angle, fixed in the normal state.…”
Section: Since Is Approximately Proportional To B ͑I ϸ K Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This question is studied in detailed in Ref. 5. It is shown that the nonuniformity of 0 ͑the decrease of the conductivity of a layer near the surface͒ increases the phase angle, fixed in the normal state.…”
Section: Since Is Approximately Proportional To B ͑I ϸ K Nmentioning
confidence: 99%
“…In addition, in these fields X͑H͒ is close to 1, and the relation ͑3͒, as already mentioned earlier, is very sensitive to the possible corrections which were neglected, including also to thermal fluctuations, which decrease the effective magnitude of pinning. 5 Figure 5 demonstrates the "quality" of the description of the amplitude of the peak effect near H C2 by the CP theory at various temperatures. This description is fully acceptable.…”
Section: Since Is Approximately Proportional To B ͑I ϸ K Nmentioning
confidence: 99%
“…The fulfillment of this condition can be considered as an independent test for the measuring procedure proposed. If this condition fails it can be due to a strong non-uniformity of the conductivity near the surface of the sample (see [5]), and in this case one cannot use the relations (6), (7) for the analysis of the results of the measurements. In the experiments presented in this paper the above mentioned condition was fulfilled with the accuracy ∼ 5%.…”
mentioning
confidence: 99%
“…In particular, under the influence of the ultrasound wave, the inertial motion of normal electrons as well as superconducting electrons leads to nonzero bulk currents via the Tolman-Stewart effect. The oscillating current radiates electromagnetic waves [6,7] so that the superconductor exhibits nonzero acousto-electric effect.…”
Section: Introductionmentioning
confidence: 99%
“…The standard time-dependent Ginzburg-Landau theory (TDGL), which contains the assumption of local equilibrium, and is formulated in the laboratory frame, is a powerful tool to study phenomena in the vicinity of the superconducting-normal phase transition. To study gyroscopes [1], gravitational wave antennae [2] and the interaction of the superconducting condensate with strong sound waves [3,4,5,6,7,8,9,10,11,12,13], where the atomic lattice is in motion, an extension to TDGL is needed to accommodate the dynamical system.…”
Section: Introductionmentioning
confidence: 99%